Sorption of PFOA onto different laboratory materials: Filter membranes and centrifuge tubes. (May 2019) - Lath, Supriya; Knight, Emma R.; Navarro, Divina A.; Kookana, Rai S.; McLaughlin, Michael J.
Abstract: Measurement and reporting of concentrations of contaminants of emerging concern such as per- and polyfluoroalkyl substances (PFASs), including perfluorooctanoic acid (PFOA), is an integral part of most investigations. Occurrence of sorption losses of PFAS analytes onto particular laboratory-ware (e.g. glass containers) has been suggested in the published literature but has not been investigated in detail. We examined sorption losses from aqueous PFOA solutions in contact with different commonly-used materials in filter units and centrifuge tubes (glass and plastics). Sorption of PFOA onto different filter membrane types ranged from 21–79% indicating that filtration can introduce a major source of error in PFOA analysis; pre-treatment of filter membranes with phosphate or methanol solutions did not improve PFOA recovery. Substantial adsorption of PFOA was also observed on tubes made from polypropylene (PP), polystyrene (PS), polycarbonate (PC), and glass where losses observed were between 32–45%, 27–35%, 16–31% and 14–24%, respectively. Contrary to suggestions in the literature, our results indicated that the greatest sorption losses for PFOA occurred on PP, whereas losses on glass tubes were much lower. Variations in ionic strength and pH did not greatly influence PFOA recovery. When PFOA concentrations were increased, the percent recovery of PFOA increased, indicating that binding sites on tube-walls were saturable. This study draws attention towards analytical bias that can occur due to sorption losses during routine procedures, and highlights the importance of testing the suitability of chosen laboratory-ware for specific PFAS analytes of interest prior to experimental use. Highlights: Sorption of PFOA onto lab-ware can cause analytical bias during routine procedures. Filtration of PFOA solutions can lead to underestimation of dissolved concentrations. Sorption losses of PFOA onto polypropylene tubes was greater than on glass tubes. Sorption losses decreased when concentrations of PFOA in test solutions increased.